Pure epithelioid angiomyolipoma of kidney in tuberous sclerosis patient: A case report and review of literature - Azar Naimi; Maryam Riahinejad; Fereshteh Mohammadizadeh; Mehrdad Hosseinpour (Archives of Medicine and Health Sciences, 2016)
The majority of renal angiomyolipoma (AML) is sporadic, and occasionally it occurs in the background of tuberous sclerosis complex. Epithelioid AML (EAML) is an uncommon variant, with uncertain behavior. We present a case of tuberous sclerosis with right large renal tumor. The tumor revealed epithelioid cells accompanied by thick wall vessels and muscular bundles in all the sections; devoid of lipocytes. Immunohistochemistry confirmed the diagnosis of epithelioid perivascular epithelioid cell tumor. Pure EAML is a rare tumor with potential malignancy. Accurate diagnosis, especially differentiation it from renal cell carcinoma, is very important for proper management of the patient.